(untitled) (Journal of the College of Education for Women, 2019)
The city of Jalawla is the administrative center of Jalawla district. It is located in the district of Khanaqin with a population of 62117 inhabitants in 2018. The city of Jalawla suffers from an imbalance in the geographical distribution of educational services among the residential neighborhoods. There are only two schools in the camp district According to the city’s population, if the city of Jalawla needs eleven kindergartens and needs one primary school, eight middle schools, two preparatory schools, three secondary schools and two vocational schools. Despite the low share of the teacher or teacher for the number of students (25) students Enrollment in schools for the school of high school athletes and school students. Which determines the number of students per division (2040) students This requires the construction of additional classes to reduce the number of students in the Division, and the criterion of distance. Most of the students travel more than the distance of the planning standards, and this is due to the imbalance in the geographical distribution of educational services in the city of Jalawla. The city of Khanaqin today needs to rebuild its schools according to the requirements of modern construction and reconstruction of damaged schools after the events of 2014 and solve the problem of double and triple hours, which in turn affected the time of lesson share with the construction of laboratory rooms that need some scientific lessons.